Teaching the Reformation: ministers and their message in Basel, 1529-1629 - Burnett, Amy Nelson (Oxford studies in historical theology, 2006)
Examining four generations of Reformed pastors who served the church of Basel in the century after the Reformation, this work focuses on the evolution of pastoral training and Reformed theology, the theory and practice of preaching, and the performance of pastoral care in both urban and rural parishes